2021
DOI: 10.3390/su13063300
|View full text |Cite
|
Sign up to set email alerts
|

The Implications and Effects of Medical Waste on Development of Sustainable Society—A Brief Review of the Literature

Abstract: The sustainable development of humanity imposes precise norms regarding the management of natural resources, their extraction, use, and the introduction in a complex, innovative circuit of the waste resulting from exploitation. The paper deals with some aspects related to the sustainable management of general medical waste on the one hand and the medical waste specific to the COVID-19 pandemic, on the other hand. Medical waste requires special treatment given its impact on the environment and on humanity. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 34 publications
(45 reference statements)
0
22
0
Order By: Relevance
“…Ultimately, it leads towards an increase in time and cost of transportation. Bucătaru et al ( 2021 ), Gur et al ( 2015 ) 3. Unskilled 3PL’s personnel Medical waste contains several contagious particles; hence, skilled and qualified staff are crucial for safe collection and transportation activities.…”
Section: Factors Hindering 3pl In Bmw Managementmentioning
confidence: 97%
“…Ultimately, it leads towards an increase in time and cost of transportation. Bucătaru et al ( 2021 ), Gur et al ( 2015 ) 3. Unskilled 3PL’s personnel Medical waste contains several contagious particles; hence, skilled and qualified staff are crucial for safe collection and transportation activities.…”
Section: Factors Hindering 3pl In Bmw Managementmentioning
confidence: 97%
“…Moreover, MWTTs depends on the development level of the country. Bucătaru et al [94], found a correlation between the different forms of MWM in different countries, which effects the processes for the collection, storage, and destruction of the HMW. Letho et al [95], found that understanding and practice of MWM by the healthcare workers decreases the lack of proper application of the National guidelines.…”
Section: Medical Waste Handlingmentioning
confidence: 99%
“…The occurrence of pharmaceutical wastes in the environment is an everyday recognized global concern (Costel et al, 2021). Medication disposal is an alarming issue today and gaining more and more awareness from healthcare professionals as well as consumers (Kadam et al, 2016).The strategic attention to grapple with Covid-19 cases will lead to multiple waste generation problems, posing another health risk if not properly handled and disposed (Alrawi et al, 2021;Ejeromedoghene, 2021).Pharmaceutical waste disposal being a critical step in the supply chain, low and high-income countries struggle to implement a disposal system that is affordable, efficient and safe (Kambaet al, 2017).The central challenge is to determine how to dispose of pharmaceutical waste in a manner that is safe for the environment and for public health while still being affordable and effective (Costel et al, 2021).Methods of pharmaceutical waste management and disposal include; incineration, secure landfilling, waste immobilization-encapsulation, waste immobilization-inertization, sewer (Jaseem et al, 2017). Pharmaceuticals are generally disposed of by incineration at high temperatures (above 1200 ° C) (Nyagah et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%